AB0232 PAIN SCORE WITH VISUAL ANALOG SCALE OF 30MM OR MORE IS A RISK FACTOR OF WORSENING CLINICAL DISEASE ACTIVITY INDEX (CDAI) AT THREE MONTHS AFTER ATTAINING CDAI REMISSION IN PATIENT WITH RHEUMATOID ARTHRITIS. (2nd June 2020) - Yoshii, I.
Abstract : Background: In treating with rheumatoid arthritis (RA), it is needless to say essential treatment goal with first priority. On the other hand, patient's pain influences on clinical indices deeply, however, pain score is not been regarded as most important despite that correlates with patient reported outcome. Objectives: Clinical significance of remnant pain score for clinical outcome although attaining remission in clinical disease activity index (CDAI) statistically. Methods: RA patient who have attained remission with CDAI were picked up. These patients were divided into two groups whether CDAI at three month after the first CDAI remission attained; namely CDAI-R or CDAI-F. Background data such as sex, age at onset, age, anti-cyclic citrullinated polypeptide antibodies (ACPA), rheumatoid factor (RF), Sharp/van der Heijde Score (SHS), clinical disease activity score (CDAI), C-reactive protein (CRP), modified Health Assessment Questionnaire score (mHAQ), and pain score with visual analog scale (PS-VAS) at first consultation, time span from the first consultation to first CDAI remission were compared between the two groups using Mann-Whitney U-test. CDAI, CRP, mHAQ, PS-VAS, and QOL value calculated from EuroQOL-5 dimension questionnaire (EQ-5D) at the time of CDAI were also statistically compared with Mann-Whitney U-test. Parameters that demonstrated statistical significance within 5% were picked up, and odds ratio for CDAI remission were calculated with binary logistic regression analysis. Moreover, parameters that demonstrated statistical significance with p-value within 5% were evaluated with receiver's observational characteristics (ROC) analysis, and cut-off index (COI) was calculated. Results: A total of 907 patients with 594 CDAI-R and 313 CAI-F were recruied. Demographic characteristics of the two groups were shown in Table 1. SHS at first consultation and time span from first consultation to CDAI remission attained demonstrated significantly less in the CDAI-R than the CDAI-F group, while the other parameters demonstrated no significant difference. CRP, CDAI, mHAQ, PS-VAS, and QOL at CDAI remission demonstrated significant difference between the CDAI-R and CDAI-F groups. With binary logistic regression analysis, CRP, CDAI, and PS-VAS demonstrated significant regression for CDAI-R with 1.68, 0.71, and 0.78 in odds ratio, respectively. COI for CDAI remission was 0.4, 1.0, and 30 for CRP (p=2.4 x 10 -4 ), CDAI (p=3.0 x 10 -32 ), and PS-VAS (p=2.4 x 10 -4 ), respectively. Conclusion: PS-VAS at the moment of CDAI remission is suggested to be predictive factor for sustaining CDAI remission at three months thereafter as well as CRP value and the CDAI score. Disclosure of Interests: None declared